2003
DOI: 10.1080/01443610310001604475
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of male infertility in southeastern Nigeria

Abstract: Three hundred and fourteen Nigerian couples were evaluated thoroughly for the cause of their infertility in our clinics located at Nnewi and Awka in Southeastern Nigeria. Two hundred and four (65.0%) of them had primary infertility and 110 (35%) had secondary infertility. The median duration of the infertility was 5 years and majority of the female patients (67.2%) were aged between 25 and 34 years. A positive male factor alone was found in 133 (42.4%) couples and female factor alone in 81 (25.8%) couples (P<0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 4 publications
(4 reference statements)
10
64
1
3
Order By: Relevance
“…In our study the infertile males and females' mean age was 38.7 (95% CI:36.7; 40.7) and 29.9 (95% CI:28.0; 31.7) years respectively. This was comparable to to two Nigerian studies that found a mean age of 39.1±6.0 for the male [9] and 31.1 years for the female partners [10]. Infertility was concentrated among women aged 25 to 34 in Nigeria [10] like in our study.…”
Section: The Prevalence Of Infertility In Ouagadougou (Burkina Faso)supporting
confidence: 79%
See 2 more Smart Citations
“…In our study the infertile males and females' mean age was 38.7 (95% CI:36.7; 40.7) and 29.9 (95% CI:28.0; 31.7) years respectively. This was comparable to to two Nigerian studies that found a mean age of 39.1±6.0 for the male [9] and 31.1 years for the female partners [10]. Infertility was concentrated among women aged 25 to 34 in Nigeria [10] like in our study.…”
Section: The Prevalence Of Infertility In Ouagadougou (Burkina Faso)supporting
confidence: 79%
“…The levels of secondary infertility ranged between 7.5-15.3% in Thailand and Vietnam and higher at up to 24% in Pakistan [18]. Studies in Benin, Cameroun and Tanzania found a secondary infertility rates between 7% and 33% and up to 35.0% in Nigeria [10].…”
Section: The Prevalence Of Infertility In Ouagadougou (Burkina Faso)mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition timing of insemination, number of insemination per cycle may influence the ultimate pregnancy [22]. To maximize the chance of success of IUI, the timing of insemination needs to be closely related to the time of ovulation, ovulation occurred at a mean time of 27.3 hour from onset of LH surge [25].…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria and some parts of sub-Saharan Africa including the Republic of Sudan and Cameroon, infertility rate could exceed 30% [3][4][5]. Some studies of South-eastern Nigeria, have demonstrated a 65% and 35% prevalent rate for primary and secondary infertility respectively [6]. Similarly, some countries, most notably Kenya, Gabon, Botswana, Zimbabwe and many other African countries, have shown a trend toward lower fertility [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%